NEUROPHYSIOLOGICAL CHARACTERISTICS OF SLEEP BRUXISM IN CHILDREN - Shadimetova N.M; Saidkhodzhayeva S. N (Scholar Express Journal, 2022)
An international panel of experts has redefined bruxism as repetitive jaw muscle activity characterized by clenching or grinding of teeth and/or tensing or thrusting of the mandible that can occur while awake (i.e., wakeful bruxism) or during sleep (i.e., sleep bruxism). Determining the nature of the phenomenon, taking into account comorbid disorders, will provide an opportunity to reduce the drug burden on the patient, and, on the other hand, to increase the effectiveness of therapy. 80 patients with sleep bruxism were examined, patient history and comorbid disorders observed in sleep bruxism were studied. EEG in 3 (3.75%) patients with bruxism revealed epileptiform activity, no specific changes were detected on polysomnograms, at the same time, there was a significantly higher proportion of awakening after falling asleep than in the control group (P<0.01). >
Keywords: Sleep Bruxism; Electroencephalography; Polysomnography; awakening